The effect of the change of football turf on knee kinematics of adolescent male football players - Zhou, B.; Li, B.; Bai, L. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to investigate the effect of the change of football turf on knee kinematics of adolescent male football players. METHODS: Thirteen adolescent male football players were tested by a portable infrared motion analysis system based on markers. The angular displacements of flexion/extension,valgus/varus and internal/external rotation were calculated respectively when players performed 90° shuttle running on artificial turf and natural turf. RESULTS: The maximum valgus angle and range of valgus/varus were larger when they were changed from artificial turf to natural turf (P<0.05). There were no significant differences in the maximum flexion angle, maximum extension angle, range of flexion/extension, maximum varus angle, maximum internal rotation angle, maximum external rotation angle and range of internal/external rotation (P>0.05). CONCLUSIONS: The change of football turf has a significant effect on knee kinematics of adolescent male football players. The risk of noncontact anterior cruciate ligament (ACL) injury is increased when players who are changed from artificial turf to natural turf.